Overexpression of eIF3a in Squamous Cell Carcinoma of the Oral Cavity and Its Putative Relation to Chemotherapy Response. (23rd April 2012) - Spilka, Rita; Laimer, Klaus; Bachmann, Felix; Spizzo, Gilbert; Vogetseder, Alexander; Wieser, Manuel; Müller, Heimo; Haybaeck, Johannes; Obrist, Peter
Abstract : The eukaryotic translation initiation factor eIF3a is one of the core subunits of the translation initiation complex eIF3, responsible for ribosomal subunit joining and mRNA recruitment to the ribosome. It is known to play an important role in general translation initiation as well as in the specific translational regulation of various gene products, among which many influence tumour development, progression, and the therapeutically important pathways of DNA damage repair. Therefore, beyond its role in protein synthesis, eIF3a is emerging as regulator in tumour pathogenesis and therapy response and, therefore, a potential tumor marker. By means of a tissue microarray (TMA) for histopathological and statistical assessment, we here show eIF3a expression in 103 cases of squamous cell carcinoma of the oral cavity (OSCC), representing tissues from 103 independent patients. A subset of the study cohort was treated with platinum based therapy. Our results show that the 170 kDa protein is upregulated in OSCC and correlates with good overall survival. Overexpressing tumors respond better to platinum-based chemotherapy, suggesting eIF3a as a putative predictive as well as prognostic tumor marker in OSCC.